Pengaruh Kepemimpinan Transformasional, Kompensasi dan Budaya Organisasi Terhadap Loyalitas Karyawan Departemen Produksi PT Herba Emas Wahidatama Purbalingga - Putri, Adelia Fatwa Meautia; Supriatin, Dyah; Barima, Hima (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2025)
The level of employee loyalty in the production department of PT Herba Emas Wahidatama Purbalingga in 2024 has decreased as evidenced by employee turnover data, si it is necessary to foster a loyal attitude in employees. The study aims to determine how much influence transformational leadership, compensation and organization culture have on employee loyalty production department at PT Herba Emas Wahidatama Purbalingga. The type of research used is quantitative with a population of 230 employees, while the sample used was 70 employees taken using non-probability sampling techniques with purposive sampling techniques for employees with possitions as operators in the processing, primary and secondary packaging sections. The data collection techniques used a questionnaire processed with SPSS 25. The result of the multiple regression analysis showed that transformational leadership had postive and significant effect on employee loyalty. Compensation had no effect on employee loyalty. Organization culture had no effect on employee loyalty. The R2 value of 0.625 indicates that the study contributed 62.5% of its influence on loyalty and remaining 37.5% was influenced by the other factors. To improve employee loyalty, PT Herba Emas Wahidatama Purbalingga pays mote attention to role superiors in emplementing transformational leadership style. Keywords: transformational leadership, compensation, organization culture, employee loyalty